SAT0108 Methotrexate and Anti-TNF Treatment Improve Endothelial Function in Patients with Rheumatoid Arthritis, Psoriatic Arthritis and Ankylosing Spondylitis. (15th July 2016) - Deyab, G.; Hokstad, I.; Småstuen, M.C.; Agewall, S.; Hollan, I.
Abstract : Background: Inflammatory rheumatic diseases (IRD) are associated with accelerated atherosclerosis, which progression is related to inflammation. One of the first stages in atherogenesis is endothelial dysfunction (ED). Objectives: We wanted to examine the effects of methotrexate (MTX) and anti-tumor necrosis factor (TNF) treatment (with or without MTX co-medication) on endothelial function (EF) in rheumatoid arthritis (RA), psoriatic arthritis (PsA) and ankylosing spondylitis (AS). Methods: From the data registry from PSARA (an observational study), we evaluated patients with RA (n=64), PsA (n=30) and AS (n=20) who completed a 6 month follow-up. All patients required treatment with either MTX monotherapy or anti-TNF±MTX, due to clinical indication. EF was assessed by finger plethysmography (RH-PAT): reactive hyperemia index (RHI) <1, 67 was considered as ED. In patients with ED at baseline (n=40), we searched for change in EF after 6 weeks and 6 months of anti-rheumatic therapy. Results: In IRD patients with ED, RHI improved from baseline to 6 weeks (mean change=0.56, p<0.005) and 6 months (mean change=0.46, p<0.005), with the greatest improvements within the RA subgroup in whom RHI significantly improved at both control visits. In PsA, RHI improved at both control visits, but the change was statistically significant only at the 6 months visits. AS patients had a statistically non-significant trend towards RHI improvement at both control visits. At 6 months, RHI improved more in the MTX group than in the anti-TNF±MTX group (mean change 0.74 vs. 0.24; p=0.010), and this difference remained statistically significant after adjustments for potential confounders. There was no significant difference between the treatment regimens at 6 weeks.Id significantly gtly greater thhe The improvement in RHI was independent of changes in disease activity and of traditional CV risk factors. Conclusions: Treatment with MTX and anti-TNF±MTX appears to relatively fast improve EF in IRD patients with ED, independently of improvement of disease activity. After 6 month, the EF improvement was more pronounced in the MTX users than in the anti TNF±MTX users. Among other factors, this might be due to a better effect of MTX on the vasculature, or due to differences in the MTX and anti-TNF±MTX populations. It remains to be examined in further studies if the lack of significant effect of the treatment on ED in AS is due to specific features of vascular disease in AS, or due to other factors, such as Type-2 error. Disclosure of Interest: None declared